Sampling efficiency of different sample units and procedures to sample spittlebug eggs - Nilakhe, Shashank S.; Paschoal, G. O.; Silva, A. A. da; Corsini, P. S. (Pesquisa Agropecuaria Brasileira, 2014)
A sampling study of spittlebug eggs in pastures of Brachiaria decumbens Stapf was conducted by using samples of 25, 50 and 75 cm2 of the pasture. The sampling efficiency of three sample units was compared by calculating the number of samples necessary to obtain a certain level of precision (proportion of standard error to mean expressed as a percentage). The sampling efficiency of 50 cm2 sample unit was poor in comparison to 25 and 75 cm2 . To obtain the same level of precision, e.g., 20%, the total pasture area to be examined was slightly smaller for 75 cm2 unit than for 25 cm2 at lower egg density (1/25 cm2);however, such advantage of the 75 cm2 disappeared at egg density of 4/25 cm2 . Based on this finding and the fact that fewer samples would be taken in the case of 75 cm2 than the 25 cm2 unit, the use of former was suggested. The distribution pattern of number of eggs per 25 or 50 cm2 of pasture fitted the negative binomial series.
Keywords: Zulia entreriana; Deois flavopicta; Cercopidae; Brachiaria decumbens; pasture